2015
DOI: 10.1371/journal.pone.0120569
|View full text |Cite
|
Sign up to set email alerts
|

Liver Resection for Non-Colorectal, Non-Carcinoid, Non-Sarcoma Metastases: A Multicenter Study

Abstract: BackgroundThe role of liver resection for non-colorectal, non-neuroendocrine, non-sarcoma (NCNNNS) metastases is ill-defined. This study aimed to examine the oncologic outcomes of liver resection in such patients.MethodsA retrospective analysis of liver resection for NCNNNS metastases was performed at two large centers. Liver resection was offered selectively in patients with stable disease. Oncologic outcomes were examined using the Kaplan-Meier method.ResultsFifty-two patients underwent liver resection for N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Most studies report on noncontemporary cohorts of patients going back to the 1980s . Only four reports relied on multi‐institutional data, including the cohort used to developed the AFC score, but are limited by selection bias, lack of power, clinical heterogeneity, and lack of generalizability. Thus, causality between prolonged survival and LR cannot be inferred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies report on noncontemporary cohorts of patients going back to the 1980s . Only four reports relied on multi‐institutional data, including the cohort used to developed the AFC score, but are limited by selection bias, lack of power, clinical heterogeneity, and lack of generalizability. Thus, causality between prolonged survival and LR cannot be inferred.…”
Section: Discussionmentioning
confidence: 99%
“…The survival benefit of hepatic resection for metastatic disease from colon cancer and neuroendocrine tumors is now established and accepted . However, the benefit of surgical treatment of noncolorectal, nonneuroendocrine liver metastases (NCNNELM) remains poorly defined and debated . Numerous studies and subsequent meta‐analyses have been published looking at liver resection (LR) for site‐specific NCNNELM .…”
Section: Introductionmentioning
confidence: 99%
“…The multivariable analysis showed that delay of a liver resection for at least six months and chemoradiotherapy after resection might be associated with an improved overall survival (OS) [18]. Martel et al, presented the results of a multicenter study which included 52 patients (seven with gastroesophageal origin) with non-colorectal, non-neuroendocrine, and non-sarcoma metastasis [19]. The five-year overall survival for patients with a liver metastasis of gastro-esophageal origin was 50%, compared to 63% for a contemporary colorectal liver metastasis cohort [19].…”
Section: Reviewmentioning
confidence: 99%
“…Martel et al, presented the results of a multicenter study which included 52 patients (seven with gastroesophageal origin) with non-colorectal, non-neuroendocrine, and non-sarcoma metastasis [19]. The five-year overall survival for patients with a liver metastasis of gastro-esophageal origin was 50%, compared to 63% for a contemporary colorectal liver metastasis cohort [19]. Adam et al, developed a prognostic model for hepatic resection for NCRNE metastasis, starting from 1452 patients from 41 French centers [20].…”
Section: Reviewmentioning
confidence: 99%
“…For Yttrium-90 SIRT, promising results are reported for breast cancer, ocular and cutaneous melanoma, renal cell carcinoma, and pancreatic cancer. Results of chemotherapy refer in most instances globally to patients in metastasised stages lacking specification of the treatment effect on liver metastases.Patient selection is the Achilles' heel of outcomes, and uniform selection criteria for treatment for each of these primaries are yet to be elucidated [5]. In order to move away from anecdotal reports towards more evidence-driven strategies, registries for non-conventional liver metastases and standardised reporting should be encouraged.…”
mentioning
confidence: 99%